2007
DOI: 10.1097/nmd.0b013e31811f4076
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Combat-Related Posttraumatic Stress Disorder Versus Noncombat-Related Posttraumatic Stress Disorder

Abstract: The goal of the study was to compare severity of combat-related posttraumatic stress disorder (PTSD) versus noncombat-related PTSD in a group known to have high rates of combat-related PTSD. Sample consisted of 255 male American Indian and Hispanic veterans with lifetime PTSD who were contacted in communities in 2 regions of the country. Measures of PTSD severity included current posttraumatic symptoms, remission from lifetime PTSD, lifetime severity of alcohol-drug related problems, and mental health treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…24 There is also evidence that veterans with combat-related PTSD have more severe symptoms than veterans with PTSD due to noncombat-related events. 25 Increased incidence of PTSD in military personnel experiencing TBI is consistent with research studies in other populations. These have concluded that development of psychiatric symptoms following TBI is relatively common, with 13%-27% exhibiting PTSD.…”
supporting
confidence: 76%
“…24 There is also evidence that veterans with combat-related PTSD have more severe symptoms than veterans with PTSD due to noncombat-related events. 25 Increased incidence of PTSD in military personnel experiencing TBI is consistent with research studies in other populations. These have concluded that development of psychiatric symptoms following TBI is relatively common, with 13%-27% exhibiting PTSD.…”
supporting
confidence: 76%
“…Combat PTSD is generally more severe and has a lower rate of remission than noncombat PTSD[51, 52]. A meta-analysis of controlled psychotherapy and psychopharmacology trials found that overall, nearly 2/3 of patients treated with exposure therapy who completed treatment no longer met criteria for PTSD, but treatment response was significantly poorer in combat compared to noncombat PTSD[53].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of controlled psychotherapy and psychopharmacology trials found that overall, nearly 2/3 of patients treated with exposure therapy who completed treatment no longer met criteria for PTSD, but treatment response was significantly poorer in combat compared to noncombat PTSD[53]. In a study of Hispanic and American Indian veterans, only 20% of 106 with combat PTSD had experienced a year or longer without symptoms since onset, in contrast to 40% of veterans with PTSD from noncombat trauma[51]. In a long-term follow-up study of over 200 Israeli combat veterans, 26 to 50% were still diagnosed with PTSD 20 years later[54].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of combat-related PTSD was found to be more severe and less likely to be in remission than noncombatrelated PTSD [28]. The comorbidity of SUD and PTSD among women is much higher and has more clinical severity than in men, and this could potentially be a result of the higher rates of violence and assault experienced by women [56][57][58].…”
Section: Nature Of Violence In the Post-traumatic Stress Disorder-submentioning
confidence: 98%
“…Structured measures utilized among comorbid samples include the Structured Clinical Interview for DSM-IV (SCID) [24 ,26 ], the Composite International Diagnostic Interview (CIDI) [18 ,27 ], the Computerized Diagnostic Interview Schedule (C-DIS) [21,28] and the Clinician-Administered Posttraumatic Stress Disorder Scale [29,30]. Each of these measures assesses the criteria denoted within the DSM-IV for PTSD-related symptoms that correspond to a DSM-IV qualifying traumatic event.…”
Section: Measurement Issues In Post-traumatic Stress Disorder and Submentioning
confidence: 99%